2008
DOI: 10.1523/jneurosci.4109-07.2008
|View full text |Cite
|
Sign up to set email alerts
|

Protein Phosphatase 1-Dependent Bidirectional Synaptic Plasticity Controls Ischemic Recovery in the Adult Brain

Abstract: Protein kinases and phosphatases can alter the impact of excitotoxicity resulting from ischemia by concurrently modulating apoptotic/ survival pathways. Here, we show that protein phosphatase 1 (PP1), known to constrain neuronal signaling and synaptic strength (Mansuy et al., 1998; Morishita et al., 2001), critically regulates neuroprotective pathways in the adult brain. When PP1 is inhibited pharmacologically or genetically, recovery from oxygen/glucose deprivation (OGD) in vitro, or ischemia in vivo is impai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 67 publications
2
23
0
Order By: Relevance
“…Indeed, coexpression of truncated PP1␣, which interacts with MEF2 but does not repress transcriptional activity, has no effect on hippocampal neuronal cell survival, which corresponds to the inability of tPP1␣ to repress MEF2-mediated transcriptional activity in these cells. Recent reports indicate that timing of PP1 activation and the type of neurotoxic stimulus are key determinants of a positive or negative role for PP1 in neuronal cell survival (18,26). This lends support to our finding that PP1␣-mediated repression of MEF2 may be a key determinant in regulation of neuronal survival.…”
Section: Discussionsupporting
confidence: 90%
“…Indeed, coexpression of truncated PP1␣, which interacts with MEF2 but does not repress transcriptional activity, has no effect on hippocampal neuronal cell survival, which corresponds to the inability of tPP1␣ to repress MEF2-mediated transcriptional activity in these cells. Recent reports indicate that timing of PP1 activation and the type of neurotoxic stimulus are key determinants of a positive or negative role for PP1 in neuronal cell survival (18,26). This lends support to our finding that PP1␣-mediated repression of MEF2 may be a key determinant in regulation of neuronal survival.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have demonstrated that PP1 is a potent memory suppressor in adult mice (Genoux et al 2002) and a negative regulator of synaptic strength and synaptic plasticity in the hippocampus (Morishita et al 2001;Jouvenceau et al 2006;Hedou et al 2008). These functions of PP1 have been postulated to be mediated primarily by the cytoplasmic pool of PP1, in particular, by PP1 in synaptic terminals.…”
Section: Discussionmentioning
confidence: 99%
“…Protein phosphatase assays were carried out as previously described (Hedou et al 2008). Hippocampi were dissected and homogenized in 3.75 mM Tris-HCl (pH 7.4), 15 mM KCl, 3.75 mM NaCl, 250 mM EDTA, 50 mM EGTA, 30% (w/v) sucrose, 30% (v/v) glycerol, protease inhibitor cocktail (Sigma), 100 mM PMSF using a Dounce homogenizer, then centrifuged (1000g, 10 min).…”
Section: Protein Phosphatase Assaymentioning
confidence: 99%
“…In this scenario, metaplasticity could promote functionally adaptive responses such as preventing potentiation of synaptic inputs to the point of excitoxicity. It is interesting to note in this context the considerable mechanistic overlap between neuroprotective preconditioning effects which prevent excitoxicity and metaplasticity [3,87,88].…”
Section: (A) Functional Implications Of Heterosynaptic Metaplasticitymentioning
confidence: 99%